Predicting marital adjustment based on marital justice and marital burnout - Fahimi , Maryam; Taghvaei , Davood (Journal of Assessment and Research in Applied Counseling (JARAC), 2022)
Background and Aim: The problem of marital adjustment is growing increasingly among people who have recently started living together, especially those who face educational problems and related conflicts in addition to the problems of other married people. Therefore, to reduce their adjustment problems, related factors should be identified. Therefore, the present study was conducted with the aim of predicting marital adjustment based on marital justice and marital burnout in married women. Methods: The statistical population of the study included 1100 married female students of Arak Azad University who were selected by a convenience sampling method. Using Cochran’s sample size determination formula, 284 people were selected as the sample. Data collection tools included Graham Spanier (1976) Dyadic Adjustment Questionnaire, Ghaffari Marital Justice Questionnaire (2013) and Pines Marital Burnout Questionnaire (1996). Data were analyzed using SPSS24 software and Pearson correlation and regression tests. Results: The results revealed that marital justice predicted 43.2% and marital burnout predicted 26.3% of changes in marital adjustment (P <0.05). Also, marital justice and marital burnout predicted a total of 52.4% of changes in marital adjustment (P <0.05). Conclusion: Marital adjustment can be predicted based on marital justice and marital burnout. According to the results, it is necessary to take organized actions by the organizations related to health and higher education system to promote marital adjustment